TINJAUAN EKSTRINSIK PADA KARYA HELGA RIF DI BAWAH LANGIT YANG SAMA - RIA DESY NASUTION (LP2MTBM MAKARIOZ, 2021)
This study aims to find out the extrinsic elements (describing religious values and moral values and describing the culturaland social values contained in the novel Under the Same Sky By Helga Rif . After research was conducted on the novelUnder the Same Sky By Helga Rif, found several extrinsic elements contained in the novel, extrinsic elements contained thatis about the background of the author (Helga Rif). The religious value contained a depiction of praying to God andsurrendering to God. The moral values contained in this novel are about a sense of responsibility, tolerance among others indifference and giving an idea of hard work. The cultural value contained in the novel is about the culture of the Hinducommunity in Bali, especially some exposures related to ngaben ceremony.